And another thing-- : Douglas Adams's Hitchhiker's guide to the galaxy, part six of three - Colfer, Eoin.; Adams, Douglas (New York : Hyperion, 2009)
In this sixth installment of the Hitchhiker's Guide to the Galaxy series, Arthur Dent has finally made it home to Earth, only to discover that it is about to be blown up ... again. What could a pantheon of unemployed gods, everyone's favorite renegade Galactic President, a lovestruck green alien, an irritating computer, and at least one very large slab of cheese have to do with all of this?
Keywords: Prefect, Ford; Dent, Arthur; Interplanetary voyages